Prevalence of entomophthoralean fungi (Entomophthoromycota) of aphids (Hemiptera: Aphididae) on solanaceous crops in Argentina - Manfrino, Romina Guadalupe; Gutierrez, Alejandra Concepción; Steinkraus, D.C.; Salto, Cesar Eduardo; Lopez Lastra, Claudia Cristina (2018)
Solanum melongena L. and Capsicum annuum L. were sampled in Argentina to determine the prevalence of fungal diseased aphids. The pathogens identified were Pandora neoaphidis (Remaudière & Hennebert) Humber and Zoophthora radicans (Brefeld) Batko (Entomophthorales: Entomophthoraceae) on aphids from eggplants; and P. neoaphidis and Entomophthora planchoniana Cornu (Entomophthorales: Entomophthoraceae) on aphids from peppers. The highest fungal prevalence was 45.5% (n = 2296) and 98.1% (n = 3212) from aphids on eggplants and peppers, respectively. In both crops, significant differences were found on number of infected aphids among developmental stages. P.neoaphidis and E. planchoniana caused epizootics in M. persicae.